Aktualisasi Etika Islam dalam Dunia Bisnis - M. Nur Asnawi (UIN Maulana Malik Ibrahim Malang, 2002)
In the context of an increasingly transparent macro life, the transcendental normative values of Islam are challenged to be able to manifest themselves in real terms. This demand seems to be a logical consequence when the reference to life is practically more dominated by value order, such as the idea of hedonism. In the economic activity that is becoming a new trend nowadays, there are many cheats, tackling friend's profession, monopoly, etc. This is evidence of hedonism. Islam gives the suggestion that in conducting its economic activity always hold fast to ethics and norm. This research explains that human economic life should be based on the teachings of God. Doing business has an ethical principle that is responsible, honesty, cling and always grateful. With ethics and norms packaging the economic activity, it will undoubtedly bring about a virtue. Such virtue will give birth to true happiness in economy. In the end this will lead to the establishment and success of the upcoming economy. Dalam konteks kehidupan makro yang semakin transparan, nilai-nilai normatif transendental Islam ditantang untuk mampu mewujudkan diri secara riil. Tuntutan ini nampaknya sebagai konsekuensi logis ketika acuan kehidupan secara praktis lebih didominasi oleh tatanan nilai nilai, seperti faham hedonisme. Dalam aktivitas ekonomi yang menjadi tren baru saaat ini, terdapat banyak kecurangan, menjegal kawan seprofesi, monopoli, dll. Hal ini merupakan bukti adanya paham hedonisme. Islam memberikan anjuran agar dalam melakukan aktifitas ekonominya senantiasa berpegang teguh pada etika dan norma. Penelitian ini memaparkan bahwa kehidupan berekonomi manusia hendaknya tetap berlandaskan pada ajaran Tuhan. Berbisnis memiliki prinsip beretika yaitu bertanggung jawab, kejujuran, berpegang teguh dan selalu bersyukur. Dengan etika dan norma sebagai kemasan dalam aktivitas perekonomian, niscaya akan melahirkan suatu kebajikan (virtue). Kebajikan tersebut akan melahirkan kebahagiaan sejati dalam berekonomi (ultimate happiness). Pada akhirnya ini akan menggiring kepada kemapanan dan kesuksesan perekonomian mendatang.